Penerapan Elliptic Curve Digital Signature Algorithm pada Tanda Tangan Digital dengan Studi Kasus Dokumen Surat – Menyurat - Aulia Nadzifarin; Asmunin Asmunin (Journal of Informatics and Computer Science (JINACS), 2022)
Changes in the pattern of human life through electronic digital media are the impact of very rapid technological developments, one of which is the change in patterns from paper to paperless. At the same time as the COVID-19 pandemic, which affected policies in most areas of employment and education, this was done online, so electronic documents were often used in every process in these fields. As in the case of administrative correspondence or other document exchange transactions. And the authenticity of the document is needed by using a mechanism, one of which is a digital signature. Digital signatures can assist in the process of maintaining the confidentiality, authentication, disclaimer, integrity and validity that signatures in a document have been sent and received. By utilizing the Elliptic Curve Digital Signature Algorithm (ECDSA) digital signature algorithm for encryption and decryption processes to improve data security and authentication. The final representation of the digital signature is applied to the correspondence document with PDF type, using the Python ECDSA programming language as the system running process. Keywords: Digital Signature, ECDSA, Encryption, Decryption, Electronic Document